1986
DOI: 10.1148/radiology.160.3.3526404
|View full text |Cite
|
Sign up to set email alerts
|

Nondilated obstructive uropathy: percutaneous nephrostomy performed to reverse renal failure.

Abstract: Ureteral obstruction can lead to renal failure without involving detectable dilatation of the calyces, renal pelvis, or ureter proximal to the obstruction. This phenomenon was noted in seven patients who had clinical obstruction that we were not able to diagnose using computed tomography (CT) or ultrasonography (US). These patients underwent percutaneous nephrostomy (PCN), which resulted in brisk diuresis and improved renal function. We obtained an accompanying antegrade urogram in these cases, which demonstra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
16
0
1

Year Published

1987
1987
2014
2014

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 54 publications
(17 citation statements)
references
References 0 publications
0
16
0
1
Order By: Relevance
“…9 Ultrasonography is commonly used in the diagnosis of calicael obstruction, however, dilatation is sometimes not seen with ultrasonography. 1,3,6,23 This might be due to poor vision of renal pelvis and ureter, which are often obscured by bowel gas. False negative might also be caused by dehydration resulting in a low urine output and thus lack of dilatation, 23 which was seen in this patient during the initial ultrasonography.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…9 Ultrasonography is commonly used in the diagnosis of calicael obstruction, however, dilatation is sometimes not seen with ultrasonography. 1,3,6,23 This might be due to poor vision of renal pelvis and ureter, which are often obscured by bowel gas. False negative might also be caused by dehydration resulting in a low urine output and thus lack of dilatation, 23 which was seen in this patient during the initial ultrasonography.…”
Section: Discussionmentioning
confidence: 99%
“…1 Bilateral ureteric obstruction because of external compression caused by retroperitoneal fibrosis or malignant disease account for 60% of these cases. [1][2][3][4][5][6] We report an unusual case of acute renal failure secondary to non-dilated bilateral ureteric obstruction from stone disease.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4][5][6][7][8] In our recent case report, we had demonstrated that a patient with dual functioning kidneys presenting with uremic symptoms and suspected to have obstructive uropathy must be presumed to necessarily have bilateral renal obstruction. 8 This is without prejudice to the findings on conventional renal imaging with ultrasound or CT. 8 In our three patients presented herein, with regard to the etiopathogenesis of NDOU, metastatic retroperitoneal malignant processes played a role in two (I and II), whereas in the third patient (III), the syndrome was most likely the result of early acute urinary obstruction.…”
Section: Discussionmentioning
confidence: 99%
“…1 However, under certain clinical circumstances, despite the presence of symptomatic renal failure from obstruction, renal imaging by ultrasound or other imaging techniques could still fail to demonstrate hydronephrosishydroureters. [2][3][4][5][6][7] This is the syndrome of non-dilated obstructive uropathy (NDOU). [2][3][4][5][6][7] This syndrome can be the result of various varied and often peculiar clinico-pathologic conditions including dehydration, hypotension, severe oliguria, acute early obstruction, and inability of the collecting system to dilate because of infiltrative metastatic abdomino-pelvic cancers and retroperitoneal fibrosis.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation